Company Bankruptcy Prediction Analysis Go Public in Indonesia during the Covid-19 Pandemic - Ida Bagus Nyoman Ramartha Putra; Ni Putu Sri Harta Mimba; Ni Made Dwi Ratnadi; Gayatri Gayatri (Budapest International Research and Critics University, 2022)
This study aims to compare bankruptcy predictions between sectors of publicly traded companies in Indonesia during the Covid-19 pandemic. This research was conducted in publicly listed companies in Indonesia in 2020. The number of samples in this study were 97 companies with details of the manufacturing sector 50 samples and the non-manufacturing sector 47 samples using the purposive sampling method. Data collection uses the documentation method. The data analysis technique used is the modified Altman Z-Score method, descriptive statistics and t-test. The results showed that of the 50 companies in the manufacturing sector, 36 of them were in the safe zone category, 10 companies were in the gray zone category and 4 companies were in the distress zone category. Meanwhile, of the 47 non-manufacturing sector companies, 30 companies are in the safe zone category, 6 companies are in the gray zone category and 11 companies are in the distress zone category. These results indicate that non-manufacturing sector companies are more affected by the Covid-19 pandemic, this is due to the majority of companies experiencing a decrease in liquidity in terms of cash flow.